Educação do campo uma política em construção: desafios para Sergipe e para o Brasil - Santos, Marilene (2013)
Analyze the effects produced by the educational policies implemented in the rural schools in the corresponding period between 1997 and 2010 in the State of Sergipe is the main objective of this thesis. The central question of the thesis is about understanding the implementation of federal programs in the rural schools in the state of Sergipe have produced changes in educational policy peasant? If present contradictions, and there from programs such possibility of overcoming the current educational context in the interests of workers in the field? For policy analysis of Rural Education in the State of Sergipe was identified and analyzed five educational programs that formed the Rural Education in the last thirteen years: the National Education Program in Agrarian Reform (PRONERA); Program Pro-Youth Field of Knowledge land, the Program in Education Quilombos; Active School Program, and the PROCAMPO - Degree in Education Field. A qualitative study and multireferential worked with both Marxist thinkers, as with researchers who develop important theories for public policy analysis in the field of political science. The research instruments used were: analysis of official documents and content of the programs, and interviews with professionals (clerks, teachers, coordinators) responsible for the implementation of educational policies. In findings highlight the Active School Program was the Field Education program present in greater number of municipalities (more than 90% of the municipalities surveyed). The Education Program in Quilombo was the only program that was not identified in any municipality, even in those who have maroon communities like Orange, Cumbia and Well Redondo. Most schools peasant still works in makeshift buildings and in extremely inappropriate. In terms of materials, most students peasants relies only on the textbook adopted for urban schools. Exceptions are only for students on programs Active School and Youth Field Pro-Knowledge of the Earth, which has proper manuals. The continuing education of teachers, essential for ensuring the success of educational policy, there was also very timely in some counties and was completely non-existent in most of them. In this matter there was always a divergent understanding among teachers and secretaries who participated in the survey. In all municipalities surveyed educational funding is borne by persons of municipal public management that are not directly tied to education. Municipalities who participated in this research and that form a representative sample of the state, (a) Secretary (a) education is responsible only for administrative actions and pedagogical therefore financial stocks are the responsibility of the departments of finance. The survey showed that in the Sergipe Rural Education as educational policy is still in an early stage of implementation, working through specific projects or programs of the federal government.